Global numerical optimization with a bi-population particle swarm optimizer - Esquivel, Susana Cecilia (2007)
This paper presents an enhanced Particle Swarm Optimizer approach, which is designed to solve numerical unconstrained optimization problems. The approach incorporates a dual population in an attempt to overcome the problem of premature convergence to local optima. The proposed algorithm is validated using standard test functions (unimodal, multi-modal, separable and nonseparable) taken from the specialized literature. The results are compared with values obtained by an algorithm representative of the state-of-the-art in the area. Our preliminary results indicate that our proposed approach is a competitive alternative to solve global optimization problems.